Singular integral operators, a brief historical overview of its evolution - Ortiz Fernández, Alejandro (2022)
In this work we give an analytical-historical view of the classical theory of singular integrals introduced by   A.P. Calderón-A. Zygmund. Emphasis is given to their applications to PDEs and to some projections of the  theory.